FILSAFAT AL-FARABI DALAM PRAKTEK PENDIDIKAN ISLAM - Sri Haryanto (LP3M Universitas Sains Al Qur'an, 2022)
This research is aimed to explore al-Farabi philosophy in the practice of Islamic education. Al-Farabi is called as “the second teacher” after Aristotle due to his ability to understand Aristotle, who was known as the first teacher in philosophy. He also was the first Moslem philosopher who tried to face and intertwine classical Greek political philosophy and Islam as well as possible. He also made effort to make the philosophy understandable under the context of religions. In this regard, Al-Farabi was also considered as the one preserving intellectual tradition of al-Kindi, although with higher competence and creativity, and more complicated sophistication and freedom thinking. While al-Kindi was prominent as literally Moslem philosopher, al-Farabi was admitted as the founder of philosophy study in Islam, which has been developed ever since. He was the Second Teacher and the next highest authority after his role-model, Aristotle. He gained fame for introducing the doctrine of “The Harmony of Plato’s and Aristotle’s Thinking.” His logical knowledge capacity is adequate and he was well-known as Abu Nashr or Abu Naser among Latin philosophers. The philosophy of al-Farabi reconstructs the practice of Islamic education with the presence of integrality of naturalist nativits with empiricist. This brings together the belief that what someone has is important and the presence of empirical experience influence. In the context of learning process, a teacher might give learning experience which develop students’ potential, talents, and interests in defining themselves in time. Key words: al-Farabi philosophy, Islamic education, Harmony